Ketamine-xylazine/tiletamine-zolazepam prolonged anesthesia in Cynomolgus monkeys - Cheah, Pike See; Low, Kiat Cheong; Mohidin, Norhani; Mohd Ali, Bariah; Myint, Maung; Abdul Latiff, Azian (Online Journal of Veterinary Research, 2007)
The physiological effects of a mixture of ketamine, xylazine, tiletamine and zolazepam (KT/XZ), in cynomolgus monkeys during 24 hr anesthesia is described. Eight were induced with ketamine IM and anesthetized with IV KT/XZ. In all, anesthesia was maintained for 24 hours with large decreases in rectal temperature, heart and respiratory rates but moderate hypotension. All monkeys recovered normally 4 hours post-anesthesia. These results suggest that KX/TZ mixture could be used for prolonged anesthesia in cynomolgus monkeys.